Reversal of Pakistani Norms: Homoeroticism and Gender - Formations in The Buddha of Suburbia by Hanif Kureishi - Malik, Haroon Afzal; Low Abdullah, Nurul Farhana (Pusat Pengajian Ilmu Kemanusiaan, 2019)
This paper aims at analyzing the same sex desire and its dynamics from a queer perspective in Kureishi’s debut novel, The Buddha of Suburbia. The most glaring omission which became a sole reason for this research is the politics of sexuality in Hanif Kureishi. The Buddha of suburbia in this regard is a seminal work in which father son relationship, same sex relationship, and matters related to incest and gender inversion form the core thematic concern of the novel. Along with exploring the aforementioned constructs, the research in hand serves as a bridge which presents a comparison of the mentality of Muslims living in England and the mindset of the Muslims living in Pakistan.